2012
DOI: 10.1890/12-0009.1
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of avian and small‐mammal response to fire severity and fire surrogate treatments in U.S. fire‐prone forests

Abstract: Abstract. Management in fire-prone ecosystems relies widely upon application of prescribed fire and/or fire surrogate (e.g., forest thinning) treatments to maintain biodiversity and ecosystem function. Recently, published literature examining wildlife response to fire and fire management has increased rapidly. However, none of this literature has been synthesized quantitatively, precluding assessment of consistent patterns of wildlife response among treatment types. Using meta-analysis, we examined the scienti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
109
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(124 citation statements)
references
References 50 publications
13
109
2
Order By: Relevance
“…Prescribed fires to reduce fuel load are employed in many parts of the world to limit the frequency and severity of potential wildfires and may even promote biodiversity if a mosaic of habitats is created [13]. Nevertheless, the localized detrimental impact of hazard-reduction burns on plant and animal communities can still be substantial.…”
Section: Introductionmentioning
confidence: 99%
“…Prescribed fires to reduce fuel load are employed in many parts of the world to limit the frequency and severity of potential wildfires and may even promote biodiversity if a mosaic of habitats is created [13]. Nevertheless, the localized detrimental impact of hazard-reduction burns on plant and animal communities can still be substantial.…”
Section: Introductionmentioning
confidence: 99%
“…Spotted owls likely forage in complex early seral forests because abundant dead trees for perch sites are available for this sit-and-wait predator (Carey and Peeler 1995) and the small mammal prey base can increase in such habitat, particularly deer mice (Peromyscus maniculatus; Zwolak 2009, Fontaine and Kennedy 2012, Borchert et al 2014. Under this study design, all spotted owl sites were confirmed occupied prior to post-fire logging.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that fire severity is a primary driver of fire influences on many ecosystem components (Knapp et al, 2009;Brown et al, 2014a), including influences on bird responses (Smucker et al, 2005;Fontaine and Kennedy, 2012;Lindenmayer et al, 2014). Thus, improving our understanding of community responses to high severity forest fires (i.e., wildfires that kill or top-kill the majority of live vegetation and consume the majority of dead organic matter) is currently of high interest to assist land managers with post-fire management decisions (Bisson et al, 2003;Beschta et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Given the vagility of birds, fire-induced changes in abundance and occupancy are likely driven by spatial responses to changes in habitat suitability (i.e., food resource and nesting site availability and structural habitat preferences; Hutto, 1995;Saab and Powell, 2005;Fontaine and Kennedy, 2012). At the extreme end, species such as Kirtland's warbler (Setophaga kirtlandii), red-cockaded woodpecker (Picoides borealis), and black-backed woodpecker (Picoides arcticus) are fire specialists, relying on wildfires to generate high suitability habitat under natural conditions (Probst, 1986;Saenz et al, 2001;Hutto et al, 2008).…”
Section: Introductionmentioning
confidence: 99%